Financing environmental policies in the South: an analysis of the Multilateral Ozone Fund and the concept of Full Incremental Costs - Frank Biermann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
The »Montreal Protocol on Substances that Deplete the Ozone Layer« obliges industrialised countries to reimburse developing countries — through new and additional resources — all agreed incremental costs incurred by them in their efforts to save the ozone layer. To this end, a Multilateral Fund was established in 1990. The Fund's decision-making procedures grant developing countries the same voting powers as industrialised countries — an almost revolutionary precedent in North-South relations. In this paper, the work of the Multilateral Ozone Fund since its inception is being analysed, with special emphasis on the development and implementation of the notion of »all agreed incremental costs« between industrialised and developing countries. Since comparable institutional settings have been stipulated in the more recent treaties on climate change and biological diversity, the paper's concluding section draws five »lessons« from ozone politics for other international environmental agreements, in particular the emerging climate regime. – – Das »Montrealer Protokoll über Stoffe, die zu einem Abbau der Ozonschicht führen « verpflichtet die Industrieländer, den Entwicklungsländern die vollen vereinbarten Mehrkosten zu ersetzen, die ihnen durch die Umsetzung des Protokolls entstehen — und zwar durch neue und zusätzliche Finanzmittel. Hierfür wurde 1990 ein Multilateraler Fonds eingerichtet, dessen Entscheidungsverfahren den Entwicklungsländern die gleichen Stimmrechte gewähren wie den Geberländern — ein nahezu revolutionär zu nennender Präzedenzfall in den Nord-Süd-Beziehungen. In diesem Paper wird die bisherige Tätigkeit des Multilateralen Fonds seit seiner Errichtung untersucht, wobei die genaue Umsetzung des Konzepts der »vollen vereinbarten Mehrkosten« im Mittelpunkt steht. Da vergleichbare institutionelle Festlegungen auch für die neueren Übereinkommen zum Schutz des Klimas und der Biodiversität getroffen wurden, werden am Ende des Beitrages aus den Erfahrungen der Ozonpolitik fünf potentiell relevante Lehren für weitere internationale Umweltvereinbarungen — inbesondere das entstehende Klimaschutzregime — gezogen.
Keywords: 300